A comprehensive kinetic investigation on sulfur deportment during nickel laterite calcination using model-free, model-fitting, and master plot approaches. (February 2023) - Sarbishei, Sahand; Tafaghodi, Leili
Graphical abstract: Highlights: Comprehensive kinetic analysis is performed by a novel approach of combining three methods. Sulfurization steps are found by model-free and master plot methods. Contracting sphere and Avrami Erofeev are identified as kinetic models of sulfurization reactions. Sulfurization reactions are found to be diffusion-controlled. Polynomial equations are obtained to predict %S in the calcine. Abstract: The rotary kiln-electric furnace process is the most common method for ferronickel production from laterite ore. Since sulfur deteriorates the mechanical properties of ferronickel, it is essential to examine the routes through which sulfur is transferred to the nickel-containing product during the extraction process. Oxidation of fuel (e.g., coal) in the calcination kiln emits SO2, which results in sulfur transfer from the gas to the calcine. In this investigation, coal combustion atmosphere was mimicked by purging N2-CO-CO2-SO2 gas mixture in the tube furnace. A comprehensive kinetic analysis on the sulfurization of nickel laterite ore was conducted to obtain a fundamental understanding of the rate of the sulfurization reactions. The kinetic investigation was performed by three approaches: model-free, model-fitting, and master plot at various processing times, temperatures, and partial pressures of SO2. The XRD and ICP analyses were used to determine the phase composition and sulfur content of the calcine, respectively. Considering the activation energy values obtained by model-free approach, the process is divided into two steps, before and after 60 min of calcination. Contracting sphere and Avrami Erofeev are identified as the most suitable kinetic models for steps 1 and 2, respectively. Considering the small values of activation energy, 1.4–5.3 kJ/mol, the sulfurization reactions are identified as diffusion-controlled mechanism.